A Dramatic Difference in Global Gene Expression between TCDD-Treated Atlantic Tomcod Larvae from the Resistant Hudson River and a Nearby Sensitive Population. (23rd August 2017) - Brown, Stuart M; Heguy, Adriana; Zappile, Paul; Chen, Hao; Goradia, Aayush; Wang, Yilan; Hao, Yuhan; Roy, Nirmal K; Vitale, Kristy; Chambers, R Christopher; Wirgin, Isaac
Abstract: Atlantic tomcod in the Hudson River Estuary bioaccumulate high hepatic burdens of environmental toxicants. Previously, we demonstrated that Hudson River tomcod developed resistance to TCDD and PCB toxicity probably through strong natural selection during their early life-stages for a variant of the Aryl Hydrocarbon Receptor2 (AHR2). Here, we evaluated the genomic consequences of the resistant genotype by comparing global gene expression in larval tomcod from the Hudson River with expression in larvae from a nearby sensitive population (Shinnecock Bay). We developed an annotated draft tomcod genome to explore the effects of multigenerational exposure to toxicants and a functionally impaired AHR2 on the transcriptome. We used the tomcod genome as a reference in RNA-Seq to compare global gene expression in tomcod larvae from the Hudson River and Shinnecock Bay after experimental exposure of larvae to graded doses of TCDD. We found dramatic differences between offspring from the two populations in the number of genes that were differentially expressed at all doses (0.01, 0.1, and 1 ppb) and even in the vehicle controls. At the two lowest TCDD doses, 250 and 1, 141 genes were differentially expressed in Shinnecock Bay larvae compared with 14 and 12, respectively, in Hudson River larvae. At the highest dose (1.0 ppb), 934 genes were differentially expressed in Shinnecock Bay larvae and 173 in Hudson River larvae, but only 28 (16%) of affected genes were shared among both populations. Given the large difference between the two populations in the number and identity of differentially expressed genes, it is likely that the AHR2 pathway interacts directly or indirectly with many genes beyond those known in the AHR2 battery and that other regulatory systems may also respond to TCDD exposure. The effects of chronic multi-generational exposure to environmental toxicants on the genome of Hudson River tomcod are much greater than previously expected.